Survey of the tick fauna and its seasonal dynamics at Abernosa - Asres, S.; Gebre-Ab, F. (Institute of Agricultural Research, 1991)
A study carried out on a government ranch in the Rift Valley, at Abernosa, Ethiopia, with the objectives of determining the tick fauna and its seasonal dynamics and the degree of susceptibility to infestation of two breeds of cattle, Boran and Boran-Friesian; carries out twelve monthly samplings, packed cell volume (PCV), live weight, tick species and sex, and tick feeding site recordings; the results determined four genera of five species of ticks, and that Boran-Friesian are found to be more susceptible to infestation than Boran herds.